QUALITY OF LIFE USING DERMATOLOGY LIFE QUALITY INDEX IN FEMALE PATIENTS WITH HIRSUTISM - ULLAH, MA; IQBAL, R; RAFIQUE, S (Biological and Clinical Sciences Research Journal, 2023)
Hirsutism affects a woman's social and quality of life in our society. The burden and magnitude of this effect vary from population to population. A local study was designed to determine the burden on our population. The Objective of this Cross-Sectional study was to determine the frequency of very large and extremely large effects on quality of life using Dermatology Life Quality Index (DLQI) in hirsute women presenting to Jinnah Hospital, Lahore. This study was conducted at the Outpatient Department of dermatology Jinnah hospital Lahore from 13th May 2014 to 12th November 2014. Females with hirsutism and age ranging from 18 to 49 years were included in the study. Hirsutism was labeled if the woman had Ferriman-Gallway (F-G) score ≥ 8 or one area score equal to 4, determined by clinical examination. Quality of life was determined using Dermatology Life Quality Index and was labeled as having a very large and extremely large effect if DLQI scores were 11-20 and 21-30, respectively. The marital and educational status will be used to stratify data and dig out effect modification. Two hundred twenty patients included in our study had a mean age of 26.38± 5.58 years ranging from 12 to 42 years. The mean Ferriman-Gallway score was 15.45± 3.5, while the mean DLQI score was 18± 5.09. Diagnosis of included women was Hyperprolactinemia (4/220, 1.8%), Congenital Adrenal Hyperplasia (5/220, 2.3%), Ovarian Tumors (8/220, 3.6%), Polycystic Ovarian Disease (135/220, 61.4%) and others (68/220, 30.9%). 97% of the included patients had some formal education. 124 (56.4%) were Unmarried, 94 (42.7%) were married, while 2 (0.9%) were divorced. On DLQI, an Extremely Large Effect was present in 85 (38.6%), a Very Large effect in 115 (52.3%) while Small Effect was observed in 20 patients. There is no effect of cause or diagnosis, marital status, or educational status of the sampled population. It is concluded that the frequency of Extremely Large Effect and Very Large effect wasobserved in more than half of the study population with hirsutism. The high burden of Extremely Large Effect on quality of life necessitates emotional and psychological rehabilitation as well as pharmacological and cosmetic methods in treating these patients.